Evaluation of a mentorship program in a department of anaesthesiology - Nakamwe, Ndeufika Twahafifwa (My University, 2021)
Background: Mentorship is a process whereby a younger individual develops and re-examines their professional and personal skills under the guidance of a senior colleague. In academic medicine it may be used to bridge the gaps between classroom theory and clinical practice. Mentorship is pivotal to the success of any academic institution or department. Aim: To describe the mentors’ and mentees’ evaluation of the mentorship program in the Department of Anaesthesiology at the University of the Witswatersrand. Setting: A prospective, contextual, descriptive research study conducted in the Department of Anaesthesiology, affiliated to the Faculty of Health Sciences of the University of the Witwatersrand. Methods: Convenience sampling of mentors and mentees attending departmental academic meetings was done. Two questionnaires, one for mentees consisting of 20 questions and one for the mentors consisting of 12 questions, were handed out. Data from returned questionnaires was entered onto a spreadsheet and analysed using differential and inferential statistics. Results: Mentees in the department of anaesthesiology perceived the mentorship program as beneficial and positive to their development, the majority of mentors on the other hand felt their mentoring was not effective. Conclusion: It is recommended that a formal mentorship program policy is established which clearly outlines what is expected of the mentors and mentees, and ensures a more uniform mentoring experience
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand. Johannesburg in partial fulfilment of the requirements for the degree of Masters of Medicine in the branch of Anaesthesiology, 2021